Microwave-Assisted Synthesis of CuO Nanoparticles Using Cordia africana Lam. Leaf Extract for 4-Nitrophenol Reduction. (30th March 2021) - Bekru, Aklilu Guale; Zelekew, Osman Ahmed; Andoshe, Dinsefa Mensur; Sabir, Fedlu Kedir; Eswaramoorthy, Rajalakshmanan
Abstract : Copper-oxide-based nanomaterials play an important role as a low-cost alternative to nanoparticles of precious metals for the catalytic reduction of 4-nitrophenols. In this study, CuO nanoparticles were synthesized by a microwave-assisted method using Cordia africana Lam. leaf extract for reduction or stabilization processes. The synthesized CuO nanoparticles (NPs) were characterized using X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). The analysis indicated that nanocrystals of the monoclinic CuO phase having a cluster of agglomerated morphology with a crystallite size of about 9 nm were synthesized. We also evaluated the catalytic performance of CuO NPs against 4-nitrophenol (4-NP) reduction. The catalyst has shown excellent performance completing the reaction within 12 min. Furthermore, the performance of CuO NPs synthesized at different pH values was investigated, and results indicated that the one synthesized at pH 7 reduced 4-NP effectively in shorter minutes compared to those obtained at higher pH values. The CuO NPs synthesized using Cordia africana Lam . leaf extract exhibited a better reducing capacity with an activity parameter constant of 75.8 min −1 ·g −1 . Thus, CuO synthesized using Cordia africana Lam. holds a potential application for the catalytic conversion of nitroarene compounds into aminoarene.